Natural Prey and Digestion Times of Toxorhynchites rutilus (Diptera: Culicidae) in Southern Florida - Campos, Raul Ernesto (2000)
Natural prey of Toxorhynchites rutilus (Coquillett) were identified from gut contents of 941 larvae collected from treeholes and tires located in an oak-palm woodland in south Florida. Twenty taxa of aquatic prey were recognized in midgut remains, in addition to eggs of Diptera from three families. Ostracods and chironomids were the most abundant aquatic prey in predators from tires, and rotifers and copepods from treeholes. Mosquito larvae accounted for only 6% of prey items from treeholes and 5% from tires. Remains of terrestrial arthropods of nine insect orders plus mites and spiders were also identified, these prey having been captured from the water surface by T. rutilus larvae. An electivity coefficient, R, was calculated for dipterous prey of each predator instar. Significant heterogeneities among R values in tires were attributable, in part, to high electivity for certain mosquito species, especially Aedes albopictus (Skuse), and for psychodid larvae, and low electivity for larvae of T. rutilus and Orthopodomyia signifera (Coquillett), a predator-resistant mosquito larva. Diets were more similar between predator instars in tires than in treeholes, where invertebrate diversity was higher. An associated laboratory study was conducted to determine how long common prey could be detected in guts after ingestion. When alternative prey were provided immediately after consumption, oligochaetes, copepods, and psychodid larvae and adults were detected in >50% of dissected T. rutilus for 8-18 h after ingestion. By contrast, if T. rutilus fourth instars were starved after ingesting test prey, identifiable remains of psychodid larvae were detectable for >30 d in most predator larvae. Thus, the assessment of T. rutilus diet by identification of midgut remains is highly dependent on the consumption of subsequent prey.